Pathological Findings of the Lung at Neonatal Autopsy in Dr. Hasan Sadikin General Hospital Bandung Period 2016-2019 - Rania Azzahra Salsazayasya Parikesit (Universitas Padjadjaran, 2021)
Background: Infanticide is a criminal act when a mother kills her child at or soon after birth. Considering whether a case has been decided as infanticide, determination of the life of the neonate at birth is imperative. Breath signs from macroscopic and microscopic approacesh and hydrostatic test are useful indicators. This study aimed to explore the lungs pathological findings at autopsy of neonates.